Efficacy and safety of immune checkpoint inhibitors rechallenge in advanced solid tumors: a systematic review and meta-analysis - Cao, Jiahui; Ding, Xinyao; Ji, Jianan; Zhang, Lin; Luo, Chengyan (Frontiers in Oncology, 2024)
IntroductionThe efficacy and safety of re-administration of immune checkpoint inhibitors (ICIs) in advanced solid tumors lacks consensus and is of great concern to clinicians. This study aimed to investigate the efficacy and adverse effects of ICIs rechallenges in advanced solid tumors.MethodsWe systematically searched the databases of PubMed, Embase, the Cochrane Library, and the China National Knowledge Infrastructure (CNKI), and screened the relevant literature according to the inclusion and exclusion criteria. Meanwhile, we conducted a meta-analysis of objective response rates (ORR), disease control rates (DCR), and immune-related adverse events (irAEs) for reuse of ICIs using Freeman-Tukey double arcsine transformation method.ResultsSixty eligible studies were included in the meta-analysis, and the results revealed that those who discontinued ICIs therapy and reused ICIs had an ORR of 21.6% [95% confidence interval (CI): 17.6, 25.7] and a DCR of 55.8% (95% CI: 50.0, 61.5). The overall incidence for grade ≥ 3 irAEs was 16.7% (95% CI: 11.8, 22.2). In the subgroup analysis, patients with renal cell carcinoma presented superior efficacy with an ORR of 30.9%, which was higher than that of melanoma (24.3%) and non-small cell lung cancer (NSCLC) (10.1%). Patients who have been treated with single-agent ICIs, re-treatment with a combination of ICIs directing different targets presents better outcomes, with ORR of 22.5% and DCR of 38%, respectively, compared with those patients who continue to use a single agent.ConclusionPatients with advanced solid tumors who have relapsed or progressed after prior treatment with ICIs may benefit from ICIs rechallenge, with a comparable incidence of grade ≥ 3 irAEs to those previously treated with ICIs.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023407409.